Rapid surficial oxidation of synthetic Fe-Ti oxides at high temperature: observations and consequences for magnetic measurements - Lattard, Dominique; Sauerzapf, Ursula; Kontny, Agnes (Geochemistry, geophysics, geosystems, 2012)
Synthetic polycrystalline samples of Fe-Ti oxides (titanomagnetite, Tmtss; ilmenite-hematitess, Ilmss; pseudobrookitess, Psbss) are very sensitive to changes in the redox conditions at high temperatures, either during synthesis experiments or during thermomagnetic measurements. For instance, exposure to air for a few seconds at the end of a synthesis run at 1300°C of a Tmtss-Ilmss sample produces surficial oxidation down to a depth of some 100 μm. This oxidation zone is well visible on backscattered electron images of polished sections through the sample pellet. It is characterized by so-called trellis “oxyexsolution” textures, i.e., fine lamellae of Ilmss within the Tmtss crystals and lamellae of Psbss within the Ilmss crystals. In this oxidation zone the newly grown Ilmss lamellae and the surrounding Tmtss are more Fe rich than the original crystals. The presence of trellis textures in the crystals of both coexisting phases, Tmtss and Ilmss, show that only short-scaled elemental transport within the crystals was involved and that equilibrium was not attained. Even though the oxidation zone is very narrow, the imprint of the new Tmtsscompositions is well recognizable in temperature-dependent magnetic susceptibility curves. In temperature-dependent saturation magnetization (MS-T) curves, however, the contribution of more Fe-rich Tmtss from the oxidation zone can be easily overseen. However, surficial oxidation of Tmtss does occur during MS-T measurements with a variable field translation balance, apparently in relation with insufficient Ar flowing around the sample. Further examples of rapid surficial oxidation of Fe-Ti oxide samples are also discussed.
Gesehen am 26.09.2018